Pengaruh Keterampilan Guru dalam Mengelola Kelas terhadap Tingkat Kedisiplinan Siswa di Sekolah Dasar - Wulandari, Widya; Agnia, Ai Siti Gina Nur; Jannatin, Elistsania; Azizah, Shifa Nur; Rostika, Deti (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study aims to analyze the effect of classroom management on discipline on learning activities in elementary schools, supporting factors and inhibiting factors in classroom management. The type of research used in this study uses qualitative research. Data collection was carried out using observation techniques and supported by literature studies. This research covers how strategic classroom management is applied by teachers effectively, such as classroom rules, interactions between teachers and students, the application of sanctions and also rewards that can affect student discipline. In the class management strategy, of course, there will be supporters and obstacles in its implementation. Supporting factors include curriculum, facilities, teachers, students and families. As for obstacles, they can occur by teachers, students, then the family environment and facility factors. The results of this study are expected to provide insight into the importance of effective classroom management in improving student discipline in the learning environment.